METODE EKSPERIMEN DITINJAU DARI KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA - Henni Susiani; Agus Suyatna; Undang Rosidin (Jurnal Pembelajaran Fisika, 2012)
This research is aimed to identify the effectiveness of guided inquiry learning through the experimental methods are viewed from Skill Process of Science (SPS) and the results of students learning, and knowing SPS relations with the results learn. Design experiments on this research use form Quasi-Eksperimental Design with type Non Equivalent Control Group Design. Engineering analysis of data SPS used data score observation to the process of learning and the testing of hypotheses test used One Sample T Test, analysis of data learn to use score N-gain and the testing of hypotheses test used Independent Sample T Test, while the testing of hypotheses relations SPS and results learn to used test Bivariate Correlation Test. Based on the research results obtained an average of SPS is greater than the specified indicator. On the results of studying, obtaining a score of N-gain an average of student learning outcomes in class experiments (guided inquiry learning) higher than the class of the control (conventional learning). While the correlation between SPS with the results of the study were very strong. The above results indicate that guided inquiry learning through the experimental method is effective when reviewed out of SPS and the results of student learning. And there is a positive and significant relationship between SPS and student learning outcomes.Keywords : Guided inkuiry, experiments, SPS, the result of the study.